Antecedents and consequences of team sensemaking capability in product development projects - Akgun, Ali E.; Keskin, Halit; Lynn, Gary; Dogan, Derya (Wiley, 2012)
With the increasing popularity of organizational sensemaking in the literature, sensemaking capability of firms attracts many researchers and practitioners from different fields. Nevertheless, sensemaking capability is rarely addressed in the new product development (NPD) project teams in the technology and innovation management literature. Specifically, we know little about what team sensemaking capability is, its ingredients and benefits, and how it works in NPD projects (e.g., its antecedents and consequences). By investigating 92 NPD project teams, we found that (1) team sensemaking capability, which is composed of internal and external communication, information gathering, information classification, building shared mental models, and taking experimental actions, has a positive impact on the information implementation and speed-to-market; (2) information implementation and speed-to-market mediate the relationship between team sensemaking capability and new product success; and (3) team sensemaking capability mediates the relationship between team processes and information implementation and partially mediates the relationship between team processes and speed-to-market. We also found that team autonomy, interpersonal trust among team members, and open-mindedness of team members positively influence the development of team sensemaking capability. Theoretical and managerial implications of the study findings are discussed.
Keywords: Structural Equation Models; Organizational Sensemaking; Learning Orientation; Interpersonal-Trust; Member Familiarity; Market-Information; Moderating Role; Performance; Innovation; Knowledge